234Th‐Based Carbon Export Flux Along the Indian GEOTRACES GI02 Section in the Arabian Sea and the Indian Ocean. Issue 3 (11th March 2018) - Subha Anand, S.; Rengarajan, R.; Sarma, V. V. S. S.
Abstract: 234 Th ( t 1/2  = 24.1 d), present in seawater, is a naturally occurring particle‐reactive radionuclide formed through the radioactive decay of its parent, 238 U ( t 1/2  = 4.47 × 10 9  years). The 234 Th: 238 U disequilibrium is exploited to quantify fluxes of elements moving out of the euphotic zone by attaching on to sinking particles. Under the Indian GEOTRACES programme, high‐resolution sampling in the upper 300 m depth was carried out at 11 stations in the Arabian Sea and the Indian Ocean during April–May 2014 from 17°N to 16°S along 65°E transect to estimate the 234 Th‐based particulate organic carbon (POC) export flux from the upper ocean. Average 234 Th fluxes integrated to 100 m depth were 2, 612 and 1, 968 dpm m −2  d −1 for the Arabian Sea and the Indian Ocean, respectively. The estimated POC export fluxes ranged from negligible to 9.0 mmol m −2  d −1, and the 234 Th‐based POC export efficiencies were <2 to 5%. For the same season, the Arabian Sea and the Bay of Bengal showed highly contrasting carbon export trends (mean: 4.0 and 0.8 mmol C m −2  d −1, respectively). The modeled POC export fluxes from in situ and satellite‐derived primary production are higher than the 234 Th‐based values for the Laws and Dunne models and are comparable for the Henson model. The modeled POC fluxes that depend on surface temperature and primary production could be further refined for the seasonal cycle in biological productivity and associated differences in trophic structure, grazing intensity, recycling efficiency, high bacterial activity, and associated dissolved organic carbon (DOC) export. Key Points: We present the first 234 Th‐based POC export flux estimates along the 65°E meridional transect in the Arabian Sea and the Indian Ocean In contrast to episodic decrease of primary production from 17°N to 16°S, 234 Th‐based POC export fluxes show high values in the Indian Ocean 234 Th deficit in subsurface depths is due to the diel vertical migration, grazing, and fecal pellet production by mesozooplankton